1988
DOI: 10.1002/jmv.1890250208
|View full text |Cite
|
Sign up to set email alerts
|

Rapid immunodiagnosis of active cytomegalovirus infection by monoclonal antibody staining of blood leucocytes

Abstract: The appearance of cytomegalovirus (CMV) antigen positive blood leucocytes (CMV antigenaemia) was investigated in 52 renal transplant recipients during the first three months after transplantation. Using a mixture of three monoclonal antibodies, CMV (immediate early) antigens were detected in cytocentrifuged blood leucocytes within 3-5 h after sampling. The results were related to virus isolation from buffy coats (CMV viraemia), serology with a sensitive enzyme-linked immunosorbent assay (ELISA), and clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
168
0
4

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(178 citation statements)
references
References 22 publications
4
168
0
4
Order By: Relevance
“…Firstly, we have changed our method for detection of CMV infection from the DEAFF 14 to detection of CMV antigenaemia; 19,20 this should greatly improve the detection of CMV infection since the antigenaemia test is more sensitive 19,20 and will detect breakthrough infection during GCV prophylaxis 21 whereas the DEAFF is especially insensitive in this context. Secondly, the period of monitoring for CMV infection has been extended up to day +180 post transplant so that late CMV disease may be predicted and GCV therapy initiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we have changed our method for detection of CMV infection from the DEAFF 14 to detection of CMV antigenaemia; 19,20 this should greatly improve the detection of CMV infection since the antigenaemia test is more sensitive 19,20 and will detect breakthrough infection during GCV prophylaxis 21 whereas the DEAFF is especially insensitive in this context. Secondly, the period of monitoring for CMV infection has been extended up to day +180 post transplant so that late CMV disease may be predicted and GCV therapy initiated.…”
Section: Discussionmentioning
confidence: 99%
“…The use of more sensitive tests such as CMV PCR 22 or antigenaemia 19,20 might have improved the outcome as might the use of short courses of GCV treatment (CMV infection-guided treatment) instead of prolonged GCV therapy (either prophylactic or pre-emptive) with its consequent toxicity. However, a recent study including a preponderance of sibling BMT patients has shown that CMV infection-guided treatment gives the same outcome as prophylactic GCV.…”
Section: Discussionmentioning
confidence: 99%
“…1 These methods include direct detection of CMV pp65 antigen (antigenemia) in peripheral blood leukocytes (PBL) 3 and detection of CMV DNA by the polymerase chain reaction in PBL, plasma or serum. 4 Based on encouraging early reports with the use of antigenemia, 1 we designed a uniform protocol of CMV antigenemia-guided pre-emptive treatment with GCV used in all our allografted adults since January 1993.…”
mentioning
confidence: 99%
“…In the present study, CMV qualitative and semi-quantitative PCRs were performed using DNA extracts from PBL. These cells were selected because during CMV infection, blood leukocytes participate in virus spreading into different organs and these cells are known as preferential sites for viral replication specially in immunocompromised hosts and latency 22 .…”
Section: Discussionmentioning
confidence: 99%